THE RELATIONSHIP BETWEEN TIME MANAGEMENT, SELF REGULATION, AND SMARTPHONE ADDICTION - Azizah, Muslihatin (Universitas PGRI Semarang, 2021)
This study aims to identify the relationship between self-regulation, time management and smartphone addiction on Public Senior High School students in North Surakarta. The data were collected from Public Senior High School 1, 5, and 8 Surakarta with samples by 283 students. The data collection technique was simple random sampling by developing three scales, i.e., self-regulation skill, time management scale, and smartphone addiction scale. This study applied two kinds of data analysis, which were descriptive analysis and regression analysis. The results of this study showed a negative relationship between self-regulation, time management, and smartphone addiction, either partially or entirely by 27.7%. The results also showed that the higher the studentâ€™s self-regulation and time management levels, the lower the level of studentâ€™s smartphone addiction.Â